Caesarea - Hysterectomy - Schneider, George (2015)
The experience with cesarean-hysterectomy of the last 20 years at the Charity Hospital of New Orleans and the Ochsner Clinic is reviewed. In this period, 1,000 and 150 cesarean-hysterectomies have been performed in the former and later institutions out of 6,600 and 1,000 cesarean operations respectively. The morbidity was 33 % at Charity and 10% at Ochsner Clinic. The commonest complication was urinary tract infection. There was no maternal mortality at the Ochsner Clinic. Mortality was 1.3 % at the Charity Hospital, but half of this could have been prevented.